Targets for high repetition rate laser facilities: needs, challenges and perspectives. (24th July 2017) - Prencipe, I.; Fuchs, J.; Pascarelli, S.; Schumacher, D. W.; Stephens, R. B.; Alexander, N. B.; Briggs, R.; Büscher, M.; Cernaianu, M. O.; Choukourov, A.; De Marco, M.; Erbe, A.; et al.
Abstract : A number of laser facilities coming online all over the world promise the capability of high-power laser experiments with shot repetition rates between 1 and 10 Hz. Target availability and technical issues related to the interaction environment could become a bottleneck for the exploitation of such facilities. In this paper, we report on target needs for three different classes of experiments: dynamic compression physics, electron transport and isochoric heating, and laser-driven particle and radiation sources. We also review some of the most challenging issues in target fabrication and high repetition rate operation. Finally, we discuss current target supply strategies and future perspectives to establish a sustainable target provision infrastructure for advanced laser facilities.